The Liver in Children With Metabolic Syndrome - D'Adamo, Ebe; Castorani, Valeria; Nobili, Valerio (Frontiers in Endocrinology, 2019)
Non-alcoholic fatty liver disease (NAFLD) is recognized as an emerging health risk in obese children and adolescents. NAFLD represents a wide spectrum of liver conditions, ranging from asyntomatic steatosis to steatohepatitis. The growing prevalence of fatty liver disease in children is associated with an increased risk of metabolic and cardiovascular complications. NAFLD is considered the hepatic manifestation of Metabolic Syndrome (MetS) and several lines of evidence have reported that children with NAFLD present one or more features of MetS. The pathogenetic mechanisms explaining the interrelationships between fatty liver disease and MetS are not clearly understood. Altough central obesity and insulin resistance seem to represent the core of the pathophysiology in both diseases, genetic susceptibility and enviromental triggers are emerging as crucial components promoting the development of NAFLD and MetS in children. In the present review we have identified and summarizied studies discussing current pathogenetic data of the association between NAFLD and MetS in children.